Cyber Notary System in the Order of Norms in Indonesia and Australia (Comparative Study in Notary Service Improvement Strategies) (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study was to determine the setting of norms about the Cyber ​​Notary system in Indonesia and Australia and to find out the differences and similarities in the Cyber ​​Notary regulatory system in both countries. This study uses a type of normative research; the theories used in this study are the theory of justice, the theory of legal certainty and comparative law theory. The approach method used is the conceptual approach, the legislative approach, and the comparative approach. Analysis of this study, using comparative analysis is to collect material according to the appropriate legal material about the problem being studied, and then compare it. Based on the results of the study that, the regulation of the norms regarding the Cyber ​​Notary system in Indonesia is in the Law, namely a. Law No. 2 of 2014 concerning changes to Law No. 30 of 2004 concerning Notary Position. b. Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE Law), c. Law No 40 of 2007 concerning Limited Liability Companies, and for Australian Countries, how many Cyber ​​Notary Arrangements are explained in the 1999 / Electronic Electronic Transaction Act Transactions Act 1999 / ETA (Australia). The difference lies in Indonesia having its own rules in which there is clearly stated authority in carrying out the profession of notaries including in connection with the identification of transactions electronically (Cyber ​​Notary), while Australia does not have its own specific rules that explain explicitly the authority of notaries in serving Cyber ​​systems. Notary, because the service mechanism is part of the form of electronic transactions that are regulated in the 1999 Electronic Transaction Act / Electronic Transaction Act 1999 / ETA. The equation is seen in the Function, the Cyber ​​Notary System is equally a government regulation in the form of public servants quickly, concisely, and has the value of legal protection on all parties. in Indonesia with the Registration of Online Companies, through the Legal Entity Administration System or abbreviated as SABH, and in Australia with the e-apostille system. In terms of its objectives, namely the implementation of the Cyber ​​Notary system in the two countries, which are both aimed at raising the potential of the economy and trade inside and outside the country.